2009
DOI: 10.4005/jjfs.91.184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anion Adsorption Characteristics of a Volcanic Ash Soil on Long-term NO3- Leaching from a Partial Clear-cut Cedar and Cypress Watershed.

Abstract: Effects of Anion Adsorption Characteristics of a Volcanic Ash Soil on Long-term NO 3 Leaching from a Partial Clear-cut Cedar and Cypress Watershed. J. Jpn. For. Soc. 91: 184 191. Long-term changes in the water quality of soil water and streamwater were monitored before and after cutting at the lower slope position in a small forested watershed composed of artificial stands of old aged Japanese cedar and cypress in the northern Kanto region in Japan. The NO 3 concentration in soil water directly reflected the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Coordinated comparisons among geographically varied catchments allow discussion not only of the climatological and hydrological influences considered in this review but also of other environmental variations such as geological setting and soil properties. For example, Urakawa et al (2009) pointed out that the NO 3 À adsorption characteristics of volcanic ash subsoil containing allophane clay affect NO 3 À leaching into streamwater of a Japanese coniferous forest. Such differences may lead to contrasting levels of NO 3 À export from forest catchments between regions with volcanic geology, such as the Japanese mountainous region, and regions lying on old continental geology, such as North America and Europe.…”
Section: Nomentioning
confidence: 99%
“…Coordinated comparisons among geographically varied catchments allow discussion not only of the climatological and hydrological influences considered in this review but also of other environmental variations such as geological setting and soil properties. For example, Urakawa et al (2009) pointed out that the NO 3 À adsorption characteristics of volcanic ash subsoil containing allophane clay affect NO 3 À leaching into streamwater of a Japanese coniferous forest. Such differences may lead to contrasting levels of NO 3 À export from forest catchments between regions with volcanic geology, such as the Japanese mountainous region, and regions lying on old continental geology, such as North America and Europe.…”
Section: Nomentioning
confidence: 99%
“…However, the stream NO 3 − concentrations in JSK were lower than the entire KIN [13,14]. Though all possible factors which can affect NO 3 − leaching such as topography [15,16], climate [8,[17][18][19][20][21], vegetation [9,22,23], soil chemistry [9,22,23], soil type [24,25], geology [26][27][28], and historical land-use and disturbance [8,9,[29][30][31] were examined, Makino et al [14] demonstrated that both the amount of N deposition and several climatic factors such as precipitation and temperature were important for regulating stream NO 3 − concentrations at baseflow conditions. Along the JSK, snow depth was also important.…”
Section: Introductionmentioning
confidence: 98%